Kefektifan Model Pembelajaran Somatic, Auditory, Visualization Intellectualy (SAVI) dalam Pembelajaran Membaca Puisi pada Mahasiswa Semester III STKIP PGRI Bandar Lampung - Angraini, Nani; Permanasari, Dian; Pani, Tio (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2023)
This research aims to describe students' ability to read poetry before and after using the somatic, auditory, visualization, intellectual learning model, third semester students at STKIP PGRI Bandar Lampung. The type of research used is quantitative research. Furthermore, this research method is an experimental method with a one group pretest-posttest design. Data collection uses a poetry reading test. Data analysis uses statistical techniques with the t-test formula. Based on the results of the research and discussion, it can be concluded that the ability of third semester students at STKIP PGRI Bandar Lampung in reading poetry before using the somatic, auditory, visualization, intellectual learning model, received a failure category with an average score of 38.11. Then, after applying the somatic, auditory, visualization, intellectual model, it received a good category with an average score of 71.6. At the 5% significance level, the t table is 2.04 and the t count is 14.29. In this case, it shows that the calculated t is greater than the t table. Based on the t test calculation, it is proven that "t" is the critical price of "t table" ("t" is greater than the critical price of "t table"). Thus, the null hypothesis (Ho) is rejected, this means that the somatic, auditory, visualization, intellectual model is effectively applied in learning to read poetry for third semester students at STKIP PGRI Bandar Lampung.